Home away from home: Examining adolescent refugees’ well-being in Australia - Mahadevan, Renuka; Jayasinghe, Maneka (My University, 2021)
This article examines the correlation of post-migration factors and in particular parental mental health with post-traumatic stress disorder (PTSD) and happiness levels of adolescent refugee migrants in Australia, with a special emphasis on associated age and gender differences. Data were sourced from the child module in the 2015–2016 Building a New Life in Australia data set. Results indicate that factors associated with happiness are quite different from those associated with PTSD and this varies across gender and the age groups of 11–14 and 15–17. For example, discrimination related to religion/culture and language have different correlation with boys’ and girls’ well-being measures. While father’s education and mental state have no significant association with any well-being measure, mothers’ education plays some role. Of concern is the intergenerational correlation of mother’s PTSD with their daughters. The results in this study caution against a one-size-fits-all approach to intervention and suggest that a targeted focus on older and younger adolescents further differentiated by gender is likely to be more effective.
Journal of Refugee Studies
Keywords: Adolescents and youth; Migration and settlement